2023
DOI: 10.1519/jpt.0000000000000400
|View full text |Cite
|
Sign up to set email alerts
|

Does the Number of Comorbidities Predict Pain and Disability in Older Adults With Chronic Low Back Pain? A Longitudinal Study With 6- and 12-Month Follow-ups

Ítalo R. Lemes,
Priscila K. Morelhão,
Arianne Verhagen
et al.

Abstract: Background and Purpose: People who live longer often live with multimorbidity. Nevertheless, whether the presence of multimorbidity affects pain and disability in older adults with chronic low back pain (LBP) remains unclear. The aim of this study was to investigate whether multimorbidity predicts pain intensity and disability at 6- and 12-month follow-ups in older adults with chronic LBP. Methods: This was a prospective, longitudinal study with 6- and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 40 publications
0
1
0
Order By: Relevance
“…We previously acknowledged the pragmatism of practitioners beginning with a smaller dose of exercise that is tolerated by their patient and then gradually increasing this up to physical activity guidelines levels (Gibbs et al, 2023) and this was supported by qualitative data in this study where multiple practitioners reported adopting this approach. Given the clear burden of co-morbidities in people with CLBP (Goodson et al, 2013;Rönnegård et al, 2022;Williams et al, 2018) and the increasing calls for a paradigm shift towards a more multimodal lifestyle approach to management (Lemes et al, 2023), we encourage more practitioners to consider the physical activity guidelines in their exercise prescription to increase the chances of secondary health benefits for their patients with CLBP.…”
Section: Discussionmentioning
confidence: 99%
“…We previously acknowledged the pragmatism of practitioners beginning with a smaller dose of exercise that is tolerated by their patient and then gradually increasing this up to physical activity guidelines levels (Gibbs et al, 2023) and this was supported by qualitative data in this study where multiple practitioners reported adopting this approach. Given the clear burden of co-morbidities in people with CLBP (Goodson et al, 2013;Rönnegård et al, 2022;Williams et al, 2018) and the increasing calls for a paradigm shift towards a more multimodal lifestyle approach to management (Lemes et al, 2023), we encourage more practitioners to consider the physical activity guidelines in their exercise prescription to increase the chances of secondary health benefits for their patients with CLBP.…”
Section: Discussionmentioning
confidence: 99%